Developing Healthcare Service Quality Model Using Servperf Scale: An Application to the Inpatient Department at RSIA Sentosa - Rumintjap, Astrid Felicia; Wandebori, Harimukti (Journal of Business and Management, 2017)
Abstract.Background:Ã‚Â With recent investment opportunities in the hospital industry and ever-increasing numbers of private hospitals each year, there is a need for a model on healthcare service quality, applied and tested on the Indonesian market through hospitals, aiming to pin-point areas of service quality shortages. Hence, an empirical study was conducted at a private hospital located in the Bogor regency, West Java.Methods:Ã‚Â The study adopted a purposive sampling method to collect responses from 117 inpatients through a self administered questionnaire, then processed through exploratory factor analysis to extract essential factors. Multiple regression and correlation tests were also executed to determine relationships between variables of the study.Results:Ã‚Â The result of factor analysis led to the formation of a hospital service quality model for inpatient department that involved 4 main factors translated into; Care Delivery Management, Personnel Performance Characteristics, Doctor-Patient Communication, and Hospital Resources & Infrastructure. The new model also proved to positively impact patientÃ¢â‚¬â„¢s overall assessment as whole. Positive relationships were also found between patientÃ¢â‚¬â„¢s overall satisfaction with value for money, return intention and recommendation behavior.Conclusion: This study has formulated a hospital service quality model that covers the important factors patients use in evaluating healthcare at the hospitalÃ¢â‚¬â„¢s inpatient department. It also provides a valid and reliable scale which hospital managers, from equal level of healthcare facility, may reference for future decisions.Ã‚Â Keywords: Exploratory Factor Analysis, Hospital Service Quality, Inpatient Department, SERVPERF